Guidelines for structuring photovoltaic solar energy projects in Colombia, focused on the department of Huila - Jiménez Castrillón, Camilo Andrés; Patarroyo Castrillón, Juan Felipe; Lara Figueroa, Derly Cibelly; Méndez Lozano, Rafael Armando (Cuadernos de Administración, 2023)
Despite international agreements reached at the United Nations Convention on Climate Change since 2015 concerning the transition to Non-Conventional Renewable Energy Sources (NCRE), Colombia, including the Department of Huila, has lagged behind other South American countries. This study aims to provide comprehensive project management guidelines for the development of photovoltaic solar energy projects in Huila and Colombia. The approach incorporates methodological elements from project management frameworks like PMI, PRINCE2, and SCRUM. The methodological design is mixed, involving a documentary analysis of energy demand and supply in Colombia and Huila, consideration of variables essential for photovoltaic solar project development, and integration of the aforementioned project management methodologies. The result is a proposal for methodological hybridization and the establishment of guidelines for structuring photovoltaic solar projects of various types, such as Distributed Generation (GD), Self-Generation and Small-Scale Power Generation (AGPE), Wholesale Power Generation (AGGE), and Large Generators. These guidelines are based on the project life cycle, procedures, activities defined in the proposed methodology, and the legal requirements stipulated in CREG 075 and CREG 174.